Same Day versus Staged Total Knee Arthroplasty: Do Cost Savings Justify the Risk? - Wilkie, Wayne; Mohamed, Nequesha; Remily, Ethan; Pastore, Mark; Nace, James; Delanois, Ronald E. (The Journal of Knee Surgery, 2020)
Same-day bilateral total knee arthroplasties (BTKAs) are associated with increased complications compared with staged procedures; however, as complication rates and lengths of stay (LOS) for same-day procedures decrease, they may become attractive alternatives to staged procedures. The void of recent nationwide studies comparing the 30-day total cost and risks of these procedures inspired this propensity matched review. Therefore, we compared 30-day outcomes in staged and same-day BTKAs occurring in 2016 and 2017 using the National Readmission Database (NRD), a nationwide database. The NRD was queried for all same-day and staged BTKA patients from January 1 to November 30 for both 2016 and 2017. Since the NRD links readmissions within one calendar year, TKAs occurring in this month were excluded to allow 30-day follow-up. Propensity matching was performed based on demographics, producing 19,334 patients in both cohorts. Thirty-day readmission, revision, and mortality rates, hospital costs, LOS, discharge dispositions, and complications were analyzed. Chi-square and Student's t-tests assessed categorical and continuous variables, respectively. A p-value of <0.05 was set as the threshold for statistical significance. The analysis demonstrated that less same-day patients were readmitted, with statistical but not clinical difference in revisions, and mortality (all p < 0.050). Higher 30-day cost ($33,522 vs. $29,053, p < 0.001), decreased total LOS (4.52 vs. 4.94 days, p < 0.001), and lower rates of PEs (0.3 vs. 1.1%, p < 0.001) and transfusions (2.1 vs. 8.5%, p < 0.001) but similar total complications (p >0.050) were associated staged compared with same-day BTKAs. The results suggest inpatient cost savings associated with same-day surgeries should be weighed against the slight increase in LOS and PEs. Ultimately, as LOS and PE rates continue to decrease from innovations and quality improvements, same-day BTKA may become an attractive alternative to staged BTKAs, especially if payer's incentive surgeons by increasing physician reimbursements.
Keywords: total knee arthroplasty; bilateral; unilateral; cost; complications